Video Games as Tools for Education - Arsa Widitiarsa Utoyo (Bina Nusantara University, 2018)
Computer and video games are a channel of evolution and productivity that is most consumed keeping the notice of scholars through a variety of disciplines. In general, computers and video games were ignored by educators. When educators considered the games, they noticed the social consequences of gambling, ignoring the remarkable educational potential of the game. This article looks at the history of educational research games and argues that the perceptive potential of games has been ignored by educators. Current developments in the game, including interactive stories, authoring tools, and digital world collaboration, suggest powerful new opportunities for educational media. Video games are an important part of improving education through its ability to force players to present realistic simulations of real-life situations. The beginning of the proper use of gaming technologies for education and training and there is no need for scientific and engineering methods to create games not only as a more realistic simulation of the physical world but to provide experience Effective learning. This document illustrates building up to date Integration of educational principles and game design into a dialogue between them and defining games that can be integrated based on design, entertainment, and educational features. The work follows a drawing tray that forms part of the framing definition and after selecting categories of design templates, before focusing on user interaction modes, from a pedagogical point of view, given its relevance to end users